The Decline of the Shabinar Khüree Monastery - Bulag, Uradyn E.; Fuerwa, Dorjraa (Kalmyk Cultural Heritage Documentation Project, University of Cambridge, 2021)
This video explores the history and current state of the Shabinar Khüre monastery in Hobogsair, once revered as the foremost and oldest monastery in the region following the eastern migration of the Torghuts from the Volga region in 1771. Traditionally held in high esteem by the Torghuts as a sacred site, the monastery has now been abandoned due to ethnic politics in 1963. In that year, amidst tensions with Kazakhs residing on the border of Hobogsair and Russia, the Hobogsair government initiated a resettlement project. As a result, Kazakhs relocated to Bayan Oboo, the location of the Shabinar Khüre monastery. This displacement led to the monastery’s abandonment, with the Mongol population and their Buddhist religious artefacts relocated separately to Büstüngu pasture and the Ikh Khüree monastery. Today, although a Kazakh neighbour is tending the abandoned building, the Shabinar Khüre monastery faces imminent demolition, resulting in a significant cultural and historical landmark for the Torghut community. This video showed the contemporary state of the monastery, shedding light on its rich history and cultural significance in the earlier periods of Torghut history.
Keywords: Shabinar Khüree Monastery; Hobogsair; Torghuts; Material Cultural Heritage